2007
DOI: 10.1073/pnas.0611296104
|View full text |Cite
|
Sign up to set email alerts
|

A sperm-specific Na + /H + exchanger (sNHE) is critical for expression and in vivo bicarbonate regulation of the soluble adenylyl cyclase (sAC)

Abstract: We previously identified a sperm-specific Na ؉ /H ؉ exchanger (sNHE) principally localized to the flagellum. Disruption of the sNHE gene in mice resulted in absolute male infertility associated with a complete loss of sperm motility. Here, we show that the sNHE-null spermatozoa fail to develop the cAMP-dependent protein tyrosine phosphorylation that coincides with the functional maturation occurring upon incubation in capacitating conditions in vitro. Both the sperm motility defect and the lack of induced prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(156 citation statements)
references
References 43 publications
2
154
0
Order By: Relevance
“…The fact that sNHE −/− sperm motility could be rescued by application of membrane permeable cAMP analogues has suggested that absence of sACY was perhaps the cause of the infertile phenotype [111]. An intriguing model was recently proposed [112] suggesting that sNHE may function as hyperpolarization activated proton extrusion mechanism since it possesses a putative voltage sensor [108,110,111,113].…”
Section: Mechanisms Of Proton Extrusion From Mammalian Spermmentioning
confidence: 99%
“…The fact that sNHE −/− sperm motility could be rescued by application of membrane permeable cAMP analogues has suggested that absence of sACY was perhaps the cause of the infertile phenotype [111]. An intriguing model was recently proposed [112] suggesting that sNHE may function as hyperpolarization activated proton extrusion mechanism since it possesses a putative voltage sensor [108,110,111,113].…”
Section: Mechanisms Of Proton Extrusion From Mammalian Spermmentioning
confidence: 99%
“…When transfected in NHE-null fibroblasts, full length sperm NHE expressed poorly. A chimeric construct with the first transmembrane domain of sperm NHE replaced by that of NHE1, however, exhibited improved expression at the plasma membrane and measurable NHE activity, suggesting that sperm NHE was indeed a functional NHE [169]. Sperm NHE KO males are infertile, and display severly diminished sperm motility but normal sperm numbers and morphology [170].…”
Section: Slc9c Familymentioning
confidence: 99%
“…Addition of ammonium chloride and cell-permeant cAMP analogues partially rescued the motility and fertility defects observed in KO sperm. Loss of sperm NHE resulted in a complete loss of full length bicarbonate-sensitive soluble adenylate cyclase (sAC) with greatly reduced bicarbonate-stimulated sAC activity [169]. sAC and sperm NHE were shown to physically interact with each other, forming a signaling complex at the sperm flagellar plasma membrane that seems to be vital for control of intracellular bicarbonate and cAMP levels, both of which are of great importance for sperm capacitation and motility [169].…”
Section: Slc9c Familymentioning
confidence: 99%
“…In sperm, we can add to this list the testis-specific Na ϩ -H ϩ exchanger that contains a putative consensus sequence for cAMP binding (71). As mentioned, immunofluorescence localization of G␣ s subunit suggests that the tmAC signaling pathway is present in the sperm plasma membrane surrounding the anterior acrosome.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%